EFEKTIVITAS MODEL PBL DISERTAI BRAINSTORMING PADA MATERI DIMENSI TIGA DI SMK NEGERI 3 PONTIANAK - Ridwan Ridwan; Yulis Jamiah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to determine the effectiveness of using mathematics learning with problem based learning model combine with brainstorming on three dimensional material of SMK Negeri 3 Pontianak. The research method used in this study is the experimental method with the type of pre-experimental design and the type of design form that is one shoot case study. The techniques used were observation techniques, measurement techniques, and indirect communication techniques with data collection tools including learning implementation observation sheets, observation sheets for student learning activities, learning outcomes tests, and student response questionnaires. From the calculation results obtained the implementation of learning with PBL model combine with brainstorming is classified as good with an average score of 3.23, student learning activities in PBL model combine with brainstorming by active with an average percentage of 76.26%, student learning completeness classical has not been fulfilled with the percentage of students who achieved the KBM score only 54.84%, and students' responses to learning with the PBL model combine with brainstorming by positive with a percentage of 74.19%. Based on the data obtained it can be concluded that the PBL model combine with brainstorming by less effective was applied in learning mathematics in the three dimensional material in class XI AK 1 of SMK Negeri 3 Pontianak. Keywords: Brainstorming, Effectiveness, Problem Based Learning, Three Dimensional Material